Dialysis Adequacy and Quality of Life in Diabetic and Non-diabetic Bangladeshi Patients on Maintenance Hemodialysis (BIRDEM Medical Journal, 2019)
Background: Quality of life (QOL) is one of the chief areas to be addressed when caring for people with end stage renal disease (ESRD). The continual excretory function of native kidneys are replaced in such patients by few hours of rapid urea clearance in a week. This study aimed to explore whether more weekly hemodialysis sessions and dialysis adequacy do actually improve parameters of QOL and if this is beneficial enough at the cost of taking additional dialysis sessions in a low income country like Bangladesh. Whether being diabetic influences QOL was also investigated.Methods: This cross-sectional study recruited 135 adults, who were on maintenance haemodialysis(MHD) for >3 months, from three dialysis centers in Dhaka from January to December, 2013. Patients with malignancy, dementia, and psychosis were excluded. Patients were interviewed once by the investigators to fill a validated Bangla version of the kidney disease quality of life short form questionnaire (KDQOL-SF-36 version 1.3) and calculate a QOL score.Results: Mean age, mean duration of chronic kidney disease (CKD) and MHD were 50±12 years, 4.9±5.1 years and 12±11.8 months respectively. Overall QOL score for the study sample was 50±17. Only 43(31.9%) patients received adequate hemodialysis (mean Kt/V=1.3) while the rest (with Kt/V